(untitled) (Research, Society and Development, 2021)
This article is aimed to investigate how a teacher develops a work methodology that takes into consideration students’ interests and participation by stimulating Children Protagonism. This study approaches class planning and organization, and how this teacher teaches and develops investigations with the children by taking into account what emerges from their daily life. The methodology used was a case study with a qualitative approach. The subject of the research was a teacher of the third grade of the primary school, and the research field, his classroom in a public school in a municipality of the Taquari Valley/RS/Brazil. Data was generated through semi-structured interviews, participating observation, field journals, and photographs, and it was analyzed through content analysis. The outcomes show that the theoretical framework on which this teacher bases the development of his work according to his teaching goals are relevant to produce a methodological edge that results in increasing students protagonism.